Clinical diagnosis and treatment of transdiaphragmatic intercostal hernia: a retrospective study based on 40 cases - Wu, Wei; Zhang, Tianzhu; Zhao, Yiguo; Xun, Xiaodong; Gao, Pengji (Frontiers in Surgery, 2025)
ObjectiveTo retrospectively analyze the clinical characteristics, diagnostic methods, and treatment strategies of transdiaphragmatic intercostal hernia (TDIH), so as to provide systematic clinical evidence for the diagnosis and treatment of TDIH.MethodsThe data of 1 patient with TDIH diagnosed in our hospital in 2024 was reviewed. Relevant case literatures were retrieved from the Pubmed database (from 1968 to 2024), CNKI, and Wanfang Data Platform (as of November 1st, 2024). Clinical data such as age, gender, predisposing factors of onset, clinical symptoms, surgical methods, and complications were collected and sorted out. Graphpad Prism9.5.1 was used for statistical analysis and graphing.ResultsA total of 40 cases of TDIH clinical data were included. The average age of the patients was 62.5 ± 13.7 years, with 30 male patients (75%) and 10 female patients (25%). Trauma was the main predisposing factor. Common clinical symptoms included dyspnea, abdominal pain, etc. The hernia sac was mostly located in the left intercostal space. Surgery was the main treatment method. 75% of the patients underwent open surgery, and 15% of the patients received minimally invasive surgery. Common hernia contents included colon, small intestine, omentum, etc. 50% of the patients had a mesh placed during the operation. 88% of the patients had no obvious postoperative complications, while 12% had complications such as pneumothorax.ConclusionTDIH is rare and prone to misdiagnosis and missed diagnosis. CT scanning is a crucial diagnostic means. Surgery is the main treatment method. Postoperative management is important. Risk factor analysis identified obesity (aHR 2.05, 95% CI 1.18–3.56) and large defect size (>5 cm; aHR 2.41, 95% CI 1.39–4.18) as independent risk factors for postoperative adverse events. In the future, more accurate diagnostic methods and individualized treatment regimens need to be explored to improve the prognosis.